2014
DOI: 10.1364/oe.23.000a27
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of light quality by DBR structure in white LED

Abstract: This study demonstrates the application of DBR structure into the remote phosphor structure to improve the angular correlated color temperature (CCT) deviation in white light-emitting diodes (WLEDs). In the experiment, the LED device with DBR structure yielded a higher luminous efficiency than a conventional structure. The CCT deviation can be improved from 1758K to 280K in a range of -70 to 70 degree and the luminous flux increases more than 10% due to the enhancement of the light extraction of the blue light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…S5c,d ). A DBR structure is suggested to be used to enhance the quality of light emission at different driving currents 24 . Also we found that the color shift at different viewing angles.…”
Section: Resultsmentioning
confidence: 99%
“…S5c,d ). A DBR structure is suggested to be used to enhance the quality of light emission at different driving currents 24 . Also we found that the color shift at different viewing angles.…”
Section: Resultsmentioning
confidence: 99%
“…Different processes can be used to deposit DBR layers, such as chemical vapor deposition [8,9], sol-gel [10,11], sputtering [5,7] and electron-beam evaporation [12][13][14]. Due to their high reflectivity and low losses, DBRs have been widely used in many areas like optical filters [15], micro-cavities [7,16], vertical-cavity surface-emitting lasers [17], photonic crystals [18], organic light emitting diodes [19] and enhancement of emitting efficiency [20,21]. However, a current limitation of the DBR is that only the high reflection under a near-normal incidence is considered, also in a limited wavelength interval.…”
Section: Introductionmentioning
confidence: 99%
“…This has become the most common approach for white light generation [9]. To achieve different color gamut, color rendering index (CRI), light quality, and efficiency specifications for various applications, many novel phosphors that increase the efficiency or color performance of LEDs have been developed [10][11][12][13]. Among the several phosphors for LED applications, yttrium aluminum garnet (YAG)-, silicate-, and nitride-based phosphors are used most widely in WLEDs because of their well developed fabrication processes and outstanding features.…”
Section: Introductionmentioning
confidence: 99%